Mobile research in marketing - Li, Hairong (Henry Stewart Talks, 2009)
Evolution of mobile research, Characteristics of mobile research, Barriers to deployment of mobile research, Applications for a mobile survey solution, Future issues of mobile research
Archived at 2022/04/11